2017
DOI: 10.3389/fmicb.2017.00469
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Bacillus amyloliquefaciens SC06 Induces Autophagy to Protect against Pathogens in Macrophages

Abstract: Probiotics are increasingly applied in popularity in both humans and animals. Decades of research has revealed their beneficial effects, including the immune modulation in intestinal pathogens inhibition. Autophagy—a cellular process that involves the delivery of cytoplasmic proteins and organelles to the lysosome for degradation and recirculation—is essential to protect cells against bacterial pathogens. However, the mechanism of probiotics-mediated autophagy and its role in the elimination of pathogens are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 81 publications
9
43
0
Order By: Relevance
“…In previous studies, our team has shown that Ba (1 × 10 8 cfu/mL) facilitated polarization of M1 macrophages and enhanced its phagocytic capacity in vitro [14]. Moreover, this probiotic strain could induce autophagy-related signaling pathway and improve growth performance of piglets [15,16]. Different strains of Bacillus amyloliquefaciens have been shown to not only improve growth performance, increase the ratio of villus height to crypt depth, and ameliorate cecal microflora in broilers [17,18], but also regulate cytokine and strengthen host immune status in fish [19].…”
Section: Discussionmentioning
confidence: 87%
“…In previous studies, our team has shown that Ba (1 × 10 8 cfu/mL) facilitated polarization of M1 macrophages and enhanced its phagocytic capacity in vitro [14]. Moreover, this probiotic strain could induce autophagy-related signaling pathway and improve growth performance of piglets [15,16]. Different strains of Bacillus amyloliquefaciens have been shown to not only improve growth performance, increase the ratio of villus height to crypt depth, and ameliorate cecal microflora in broilers [17,18], but also regulate cytokine and strengthen host immune status in fish [19].…”
Section: Discussionmentioning
confidence: 87%
“…The relationship between probiotics and improved gut health has received considerable scientific interest for more than a century. To protect animal guts, scientists have shown that probiotics, such as Lactobacillus, Bifidobacterium , and Bacillus , prevent gut bacterial disease (Barba-Vidal et al, 2017 ; Nishida et al, 2017 ; Wu et al, 2017 ). In the present study, L. plantarum G83 was isolated from the feces of healthy giant panda and confirmed beneficial in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Specific T cells can also stimulate autophagic activity in M. tuberculosis -infected human macrophages ( 44 ). Finally, microbiota may influence autophagy response too, as recently, probiotic Bacillus amyloliquefaciens has been shown to upregulate autophagy genes in macrophages, which lead to enhanced Escherichia coli killing ( 45 ).…”
Section: Autophagy Machinery In Macrophage Antibacterial Defensesmentioning
confidence: 99%